2014
DOI: 10.7205/milmed-d-13-00551
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Mental Health Correlates of Sleep Disruption Among Military Members Serving in a Combat Zone

Abstract: Sleep disruption is an emergent military health issue, but remarkably little is known of its prevalence or comorbidities in the combat zone. This study was designed to quantify the prevalence and mental health correlates of sleep disruption among military personnel serving within a ground combat zone during Operation Enduring Freedom. This was a large, cross-sectional survey of active duty and reserve U.S. Navy personnel (N = 3,175). Self-reported sleep measures included total hours of sleep per day, total hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 44 publications
3
38
1
Order By: Relevance
“…Military service usually includes some inevitable reductions in sleep quality and restrictions in time available to sleep, and a buffering effect of hardiness might partly explain why hardy service members fare better during conditions of semi-sleep deprivation and low sleep quality. In addition, research shows that active-duty soldiers experience widespread sleep disruption (Taylor et al, 2014). Given this pattern, our findings provide a plausible explanation for why hardy military personnel display increased military performance.…”
Section: Sleep and Military Performance -The Use Of Hardiness In Perssupporting
confidence: 60%
“…Military service usually includes some inevitable reductions in sleep quality and restrictions in time available to sleep, and a buffering effect of hardiness might partly explain why hardy service members fare better during conditions of semi-sleep deprivation and low sleep quality. In addition, research shows that active-duty soldiers experience widespread sleep disruption (Taylor et al, 2014). Given this pattern, our findings provide a plausible explanation for why hardy military personnel display increased military performance.…”
Section: Sleep and Military Performance -The Use Of Hardiness In Perssupporting
confidence: 60%
“…[19, 20] As expected, from the univariate models the psychiatric disorders (PTSD, MDD, GAD, PD and AUD), as well as insomnia, each predicted SI on their own. However, these models do not account for the overlapping variance that is shared between disorders.…”
Section: Discussionmentioning
confidence: 57%
“…Insomnia is a prevalent problem among military cohorts both during and following deployment [19, 20], and has been linked to suicidal ideation (SI), attempts, and completed suicide in both military and civilian populations [2, 2130]. Data obtained from the Deployment Life Study [31] demonstrated that nearly half of their sample (48.6%) exceeded the clinically significant threshold for sleep problems [32].…”
Section: Introductionmentioning
confidence: 99%
“…The most common form of data collection in relation to the sleep habits of military personnel are questionnaires. Questionnaires include the Pittsburgh sleep quality index [304], sleep disorder scale [305], Epworth sleepiness scale [306], the Bergen insomnia scale [307], the Stanford sleepiness scale [308] and other self-report methods [309]. As already discussed, a lack of sleep can cause many issues, especially on-board navy vessels.…”
Section: Fatiguementioning
confidence: 99%